Extra-euro area manufacturing import prices and exchange rate pass-through - Robert Anderton (European Central Bank (ECB), 2003)
This paper uses a model of import prices whereby exporters to the euro area set export prices partly as a mark-up on their production costs (i.e., the degree of exchange rate pass-through) and partly in line with euro area producer prices (i.e., pricing-to-market). Using both time series and panel estimation techniques, the econometric results suggest that the pass through of changes in the effective exchange rate of the euro to the price of extra-euro area imports of manufactures is around 50% - 70%, while pricing-to-market has an estimated weight of between 50% - 30%. We also find some evidence of differences across import suppliers, with EU member states who are not part of the euro area assigning a relatively larger weight to pricing-to-market, while euro area imports from the United States seem to be characterised by a relatively higher degree of exchange rate pass-through.
Keywords: D40; E30; F10; F31; 330